Hubungan Komunikasi Interpersonal terhadap Penyesuaian Diri pada Siswa - Wulandari, Anisa Aulia; Istiadah, Feida Noorlaila; Imaduddin, Aam (Student Journal of Guidance and Counseling, 2025)
This research was conducted on class This type of research is quantitative research with a correlational approach. Data collection techniques use interpersonal communication and self-adjustment questionnaires. The sampling technique used in this research was Non-Probability sampling with a sample size of 201 people. Based on research results. Based on research results and data analysis using IBM SPSS Statistics Version 24 software, it produces a value of 0.167* meaning that there is a positive relationship between interpersonal communication and self-adjustment in students at SMA Negeri 1 Manonjaya with a significance of 0.018. Significance can be interpreted as meaning that if the correlation is compared with population conditions, it will be the same. From the results of the correlation test above, there is a very weak relationship between interpersonal communication and self-adjustment. The results of the correlation test above show a positive correlation relationship. However, because the relationship is in the very low category, it can be interpreted that if interpersonal communication increases, it only slightly predicts a decrease in personal adjustment.